Assessment of outcomes of elective cancer surgeries in children during coronavirus disease 2019 pandemic: Retrospective cohort study from a tertiary cancer center in India. Issue 35 (3rd September 2021) - Qureshi, Sajid S.; Ramraj, Deepak; Chinnaswamy, Girish; Parambil, Badira C.; Prasad, Maya; Amin, Nayana; Ramanathan, Subramaniam; Khanna, Nehal; Laskar, Siddharth
Abstract : Abstract: To describe the outcomes of elective cancer surgeries and adverse consequences on the patients and medical staff due to the surgical interventions in children during the Coronavirus Disease 2019 (COVID-19) pandemic. The study included children younger than 15 years who underwent elective cancer surgeries from March 4, 2020 and December 3, 2020. A total of 121 patients (62% male; median age, 3 years) underwent surgery. The surgical procedures included nephrectomies (n = 18), neuroblastoma (n = 26) and soft tissue tumor resections (n = 24) and complex surgical procedures like extended liver resections (n = 2), intra-atrial thrombectomy under cardiopulmonary bypass (n = 2), pancreatoduodenectomy (n = 1), and free microvascular flaps (n = 7). Clavien-Dindo Grade III complications were 5% (n = 6), and there were no postoperative deaths. Preoperative COVID-19 testing was performed in 82% of children, and only 2% showed severe acute respiratory syndrome coronavirus 2 positivity. Postoperatively, 26 children were tested because of specific symptoms and, 6 tested positive for severe acute respiratory syndrome coronavirus 2. Except for a median delay of 23 days in treatment, none of the patients with COVID-19 required critical hospital management. None of the surgical residents or faculty acquired COVID-19, while 4 each medical and support staff were tested positive in the study period. COVID-19 was not a deterrent for continued cancer care, and surgeries could be safely performed adopting universal preventive measures without any added morbidity from COVID-19. Caregivers and centers dealing with childhood cancers can be encouraged to sustain or seek early healthcare.